Perkembangan Fisik Motorik Anak Usia Dini Kelompok B di TK Padma Mandiri Way Halim Bandar Lampung - Putri, Destria Arista; Herpratiwi, Herpratiwi; Pamungkas, A; Harianto, J. (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Early childhood is a very sensitive age range in the development of a child. Growth and development are very important aspects that parents pay attention to their children. This study aims to describe the gross motor physical development of children through games in Padma Mandiri Kindergarten. This research is a research using descriptive qualitative method. Sources of research data obtained from primary data and secondary data. The researcher obtained primary data from interviews with school principals and B1 class teachers at Padma Mandiri Kindergarten as well as observations of children's gross motor physical development. Secondary data was obtained from the results of documentation in the form of photographs of children's physical motor development at Padma Mandiri Kindergarten. The data obtained is then collected, reduced, described, tested for the validity of the data and concluded. The results showed that the physical motor developmentof children in Padma Mandiri Kindergarten was very effective because it was given a stimulus in the gross motor development of children by using the playing method, there were twelve children who developed very well fulfilling the four existing indicators, the children developed very well in jumping, running, throwing, tiptoeing, and one child was found who had not developed because it did not meet the four existing indicators, the child had not yet developed in jumping, running, throwing, and tiptoe